Imidazole Containing Natural Products as Antimicrobial Agents: A Review - K. Gupta, Girish; Kumar, Vinod; Kaur, Kamalneet (Natural Products Journal, The, 2014)
Imidazoles, natural or synthetic constitute an important class of bioactive heterocycles which have been found more effective in the treatment of various infectious and life threatening diseases. They exhibit a broad spectrum of biological activities such as anti-diabetic, antiviral, anticancer, anti-inflammatory, antibacterial and antifungal etc. The purpose of this review is to provide an overall update of the imidazole containing natural products mainly possessing antifungal and antibacterial activities till 2014.
Keywords: natural product